TONE TEACHING PLAN DESIGNED FOR INDONESIAN CHINESE BEGINNERS - Candra, Haryono (English Department FBS UNP, 2019)
Chinese is a tonal language, and Chinese tones can differentiate meanings of Chinese characters. In contrast, Indonesian is a language without tones, which explains why Indonesians have trouble acquiring tones when beginning to learn Chinese. Having recognized the importance of Chinese tones in teaching Indonesian beginners Chinese, we propose in this article a tone teaching plan designed for Indonesian Chinese beginners based on detailed analysis of previous research. The plan was tested at the Pahoa School in Tangerang District, Jakarta, Indonesia. The participants were 74 middle school students who had never learnt Chinese before. After the experiment, the questionnaires were used to collect data. It was found that this teaching plan was effective. In terms of mono-syllable adjustment, most students can make four tones of Chinese, especially rising tones and falling-rising tones; In terms of bisyllable tone sandhi, most students can master the law of tone change. However, this teaching plan also has some shortcomings. For example, the forms of tone teaching and training are not diversified; the design of the neutral tones teaching is not comprehensive enough; and the distribution of tone teaching items is uneven. These drawbacks can be further improved in future research.